Assessment of Groundwater Quality of Taluka Bulri Shah Karim, District Tando Muhammad Khan, Sindh, Pakistan - Ghulam Murtaza Arain; Nazia Sattar; Sumaira Khatoon; Javed Mustaquim (International Journal of Economic and Environment Geology)
Groundwater in Pakistan is the main drinking water source, highlighting the significance of regularly monitoring its quality. There have been several examples of high concentrations of elements like arsenic and nitrate in groundwater that harm human health and the environment. Our aim with this study was to assess the groundwater quality of the sub-district Bhulri Shah Karim for drinking and irrigation purposes. We collected groundwater samples from 53 shallow bore well hand pumps in October and November 2018. We determined the concentration of four cations, five anions and other parameters like pH, turbidity, TDS, total hardness, EC, alkalinity, total iron, and arsenic. The groundwater was found to be very hard, and the relative abundance of cations and anions was Na+> Ca2+> Mg2+> K+ and Cl‾ > HCO3‾ > SO42‾ > NO3‾ > F‾. The concentrations of arsenic and iron varied from 0 to 0.2 mg/L and 0.02 to 3.6 mg/L, respectively. We discussed groundwater quality for drinking and irrigation purposes by calculating the water quality index, sodium adsorption ratio, percent of sodium, permeability index, and residual sodium carbonate. In conclusion, the groundwater of the studied area is suitable for drinking on average and irrigation. However, some water samples were high in arsenic content, and some were highly saline and may need some prior treatment